The Selection of Best Employee by using Analytical Hierarchy Process Method in Go Wet Water Park - Supriyanti, Supriyanti; Destiana, Henny (Politeknik Ganesha Medan, 2019)
In a company, human resource is something that must really be considered, the company must have good quality of human resources and be able to work well so that the company's sustainability can be maintained. To maintain the quality and existence of its employees, the company needs to give appreciation to its employees so that employees are motivated to work better. Employees are not motivated to work better because there is no model employee selection yet. Selecting and determining model employees requires a method or decision support system to support the selection of model employees. There are many methods that can be used to select model employees, one of which is the Analytical Hierarchy Process method. To support the selection of model employees, software that can make it easier to determine model employees is needed. The software used is Expert Choice 2000 software. The results obtained from research on the selection of model employees using the Analytical Hierarchy Process method in Go Wet Water Park are employees named Nugraha successfully selected as a model employee in the company with an overall inconsistency of 0.1.